2014
DOI: 10.1021/nl404289z
|View full text |Cite
|
Sign up to set email alerts
|

Aligned Epitaxial SnO2 Nanowires on Sapphire: Growth and Device Applications

Abstract: Semiconducting SnO2 nanowires have been used to demonstrate high-quality field-effect transistors, optically transparent devices, photodetectors, and gas sensors. However, controllable assembly of rutile SnO2 nanowires is necessary for scalable and practical device applications. Here, we demonstrate aligned, planar SnO2 nanowires grown on A-plane, M-plane, and R-plane sapphire substrates. These parallel nanowires can reach 100 μm in length with sufficient density to be patterned photolithographically for field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
79
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 51 publications
6
79
0
Order By: Relevance
“…It can be seen from Table that most photodetectors with high value of EQE and R λ are measured at bias from 1 to 20 V . The devices fabricated from SnO 2 nanowires, ZnO‐Nanorod/CuSCN, TiO 2 nanorod arrays and Ag‐ZnO nanowires measured at nominal zero bias show low values of EQE and R λ . However, the individual SnO 2 nanowire‐based photodetectors D1 and D2 in the present work show both high performances and self‐powered properties.…”
Section: Resultsmentioning
confidence: 99%
“…It can be seen from Table that most photodetectors with high value of EQE and R λ are measured at bias from 1 to 20 V . The devices fabricated from SnO 2 nanowires, ZnO‐Nanorod/CuSCN, TiO 2 nanorod arrays and Ag‐ZnO nanowires measured at nominal zero bias show low values of EQE and R λ . However, the individual SnO 2 nanowire‐based photodetectors D1 and D2 in the present work show both high performances and self‐powered properties.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison with other strategies of the fabrication of MOS gas sensors with microhotplatforms and nano-sized SnO 2 as a sensitive material1516171831323335, our strategy is of lower cost, batch production, and more controllability. Not only the size, sensitive material, and doped catalysts can be well controlled, but the working temperature, sensitivity, and detection limit can be also controlled.…”
Section: Discussionmentioning
confidence: 99%
“…Due to these distinct advantages, much effort has geared towards the fabrication process of such nanostructured gas sensing materials. Many nanostructured materials such as nanoparticles45, nanotubes678910, nanowires111213141516171819, and hollow spheres202122 have been extensively researched for various gas sensing applications. In particular, nanostructured materials of metal oxide semiconductor (MOS), which possess remarkably high sensitivity and a large detection range to a variety of gases23, have been widely researched in recent decades and are expected to be deployed in domestic, industries, aerospace, and military applications6242526272829.…”
mentioning
confidence: 99%
“…18 For the C-plane, which has higher symmetry, the 6-fold symmetric alignment is the same for ZnO 16 and GaN 17 NWs; however, no alignment was reported for CNTs. It was suggested that this is due to the high symmetry of C-plane sapphire, 10 which presumably does not produce strong enough anisotropy.…”
Section: ■ Introductionmentioning
confidence: 97%